Bubble nucleation, micro-explosion and residue formation in superheated jatropha oil droplet: The phenomena of vapor plume and vapor cloud. (1st February 2020) - Wang, Jigang; Qiao, Xinqi; Ju, Dehao; Sun, Chunhua; Wang, Tengfei
Highlights: Evaporation induced vapor plume and vapor cloud are first observed. Chemical reactions occurred during the evaporation process of JO droplet. The residue volume decreases with the increase of ambient temperature. The micro-explosion of secondary droplets are similar to the parent droplet. Bubble nucleation in JO droplet contains four modes. Abstract: The evaporation and secondary atomization of droplets in cylinder has been confirmed to be one of major factors determining combustion efficiency. Experiments were carried out to elucidate the bubble nucleation and micro-explosion characteristics of superheated jatropha oil (JO) droplet during evaporation process at 873, 973, 1073 K and atmospheric pressure. A single droplet was placed at the intersection of two quartz fiber and introduced rapidly into a high temperature chamber. Several interesting features such as bubble nucleation, bubble growth and coalescence, puffing, vapor jetting, droplet jetting, surface pit, floating raft and micro-explosion were observed. Two different types of micro-explosion, namely global and local micro-explosion were identified. It was also found that chemical reactions occurred during the evaporation process of JO droplet. Bubbles in JO droplet were produced partly by superheating of low boiling point fatty acid and partly by pyrolysis of long-chain fatty acids. There were four modes of bubble nucleation in JO droplet: surface pit nucleation, particle-droplet interface nucleation, fiber-droplet interface nucleation, and floating raft interface nucleation. Surface pit nucleation and floating raft interface nucleation were the main mode. The evaporation residue formed at the end of evaporation, which was caused by the polymerization and aromatization reactions. Most importantly, vapor plume and vapor cloud induced by evaporation have been discovered for the first time. Vapor loud was very similar to the liquid state in the dilute spray region. These were mainly due to the non-isothermal condensation caused by Stefan outflow.